1999
DOI: 10.1046/j.1365-263x.1999.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

A nasopalatine cyst in an 8‐year‐old child

Abstract: The nasopalatine cyst (NPC) was first described in 1914 and it is considered the most common non-odontogenic cyst. Most studies show a higher incidence of NPC among males than females, with a male/female ratio of 1.7:1. The majority of the cases described in people in their fifth decade involve Afro-Caribbeans, while those in their sixth decade are mainly caucasians. These cysts are normally asymptomatic, unless they are infected. The most commonly reported clinical symptom is swelling in the anterior part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…The nomenclature of these cysts should be based on etiophatogenesis rather than anatomic location. Based on the results of the present study, the correct nomenclature would be a nasopalatine duct cyst, which corroborates with a number of studies found in the literature 1,4,6,8,10,11,17,20-24 . …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The nomenclature of these cysts should be based on etiophatogenesis rather than anatomic location. Based on the results of the present study, the correct nomenclature would be a nasopalatine duct cyst, which corroborates with a number of studies found in the literature 1,4,6,8,10,11,17,20-24 . …”
Section: Discussionsupporting
confidence: 91%
“…The observation of epithelial remnants in the nasopalatine duct near the incisive papilla in human fetuses suggests the possibility that incisive papilla cysts originate from the embryological remains of the nasopalatine duct. This brings into question the denomination of a cyst in the nasopalatine region as a nasopalatine canal cyst, nasopalatine cyst or median palatine cyst 8,10,17,24 . The nomenclature of these cysts should be based on etiophatogenesis rather than anatomic location.…”
Section: Discussionmentioning
confidence: 99%
“…The other aspect of the case is the presence of a mesiodens which is a supernumerary tooth reported in literature with a higher Asian prevalence [4]. These teeth either erupt or remain impacted and can often cause problems such as malocclusion or give rise to tumors or cysts.…”
Section: Resultsmentioning
confidence: 94%
“…The term NPDC is now preferred to the synonymous 'incisive canal cyst' because it may occur within the nasopalatine canal or in the soft tissues of the palate or, at the opening of the canal [3]. Most cases occur in the third to the sixth decades but some have also been reported in the first decade [4]. NPDC from a periapical lesion [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggestedthat the mucous glands within the lining may causecyst formation as a result of mucin secretion. 7,9,10 Most of these cysts are asymptomatic or cause suchminor symptoms such as swelling in relation to anterior palate near incisive papilla or it may occur in the midline on the labial aspectof the alveolar ridge. The cyst may produce bulgingof the floor of nose.…”
Section: Discussionmentioning
confidence: 99%